The Effect of Red Fruit Oil on Maximum Physical Activity on Leukocyte Counts - Yohanis Manfred Mandosir; I Putu Eka Wijaya Putra; Budi Kristanto (Formosa Journal of Science and Technology, 2023)
The purpose of this study was to determine the effect of giving red fruit oil on maximum physical activity and the number of leukocytes. This type of research is quasi-experimental with a randomized pretest and posttest design. The sample for this research is 10 (ten) people who are students of the Sports Science Study Program at the Faculty of Sports Science, University of Cenderawasih. Furthermore, the data were processed with statistics at a significance level of 5% with the help of the SPSS version 22 program. The results showed that: 1) in the group given red fruit oil, there was an increase in the number of leukocytes, which was less before maximum exercise than in the group not given red fruit oil; and 2) in the group given red fruit oil, there was a decrease in the number of leukocytes after maximal exercise compared to the group not given red fruit oil.